Value Based Intermediation (VBI) as a Sharia Banking Strategy in Supporting Sustainable Development in Indonesia - Sandra Dewi; Yaswirman Yaswirman; Helmi Helmi (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
The implementation of SDGs is in line with the principles of Islamic teachings that prohibit destruction on earth (ifsad fil-ardhi), both physical damage and non-physical damage.Â  In addition, the principle of sustainability, in accordance with Maqashid Sharia by maintaining religion, preserving the soul, maintainingÂ  reason, or nurturing offspring, and maintaining property. The application of Islamic economics and finance is no different from the SDGs. The role of Islamic economy and finance strengthens the target of SDGs, one of which is by implementing Value Based Intermediation (VBI).Value Based Intermediation (VBI) aims to reorient the business model of Islamic finance with the aim of realizing the objectives of sharia so that it can generate positive and sustainable impacts for the economy, society, and the environment through practices, processes, offers, and behaviors. Value-based intermediation (VBI) aims to deliver the desired outcomes of Sharia through practices, behaviours and offerings that generate positive and sustainable impacts on society, economy, community and environment, consistent with sustainable shareholder benefits as well as long-term interests. VBI also emphasizes on minimizing and preventing negative impacts arising from the practices, behaviors, and offerings of the Islamic banking industry.The expected results of Sharia focus on improving people's welfare through the preservation of people's wealth, faith, life, offspring, and intelligence in accordance with the maqasid of Sharia. In the context of Islamic finance business, one of which is Islamic banking focuses on encouraging to generate, accumulate, and distribute wealth fairly.